Women on the Board: The Impact of Political Connections and Gender Diversity on Sustainability Reporting - Moch Mohtar; Bambang Sugeng; Puji Handayati (Institut Agama Islam Negeri Madura, 2025)
This investigation aims to analyze the influence of gender diversity and political connections on sustainability reporting disclosures in Indonesia between 2019 and 2023. This investigation utilized purposive sampling, yielding a total of 161 units of analysis. The analysis conducted in this study comprised descriptive statistics and panel data regression, employing E-Views 12 software for the computations. The findings of this study indicate that gender diversity has a positive and significant impact on sustainability reporting disclosure. At the same time, political affiliations have no impact on the transparency of sustainability reporting. The control variables of CEO narcissism and audit committee have a positive and significant effect on sustainability reporting disclosure, while CEO traits and firm size do not influence sustainability reporting disclosure. This study indicates that to improve the precision of findings, subsequent inquiries ought to be carried out over a longer period.